THE CONCEPT OF «WOMAN» IN THE STATICS AND DYNAMICS OF PHRASEOLOGY OF THE ENGLISH LANGUAGE (Academicia Globe: Inderscience Research, 2021)
The article deals with the study of gender stereotypes represented in the phraseological system of the English language, considering the semantic characteristics of gender stereotypes in the traditional consciousness of people.